(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
Scholars’ theories on the wondrous nature of the Holy Quran vary. Researchers views in proving and attesting the inimitability of the Quran with evidence and divine eloquence are various. The strongest view in proving this wondrous nature is the one which benefits from the constituents of language; studies the expression elements that form the text; depends on the different sciences of rhetoric with its technical, aesthetic, and wide impact inside the texts; as well as the composition of the text, its style, phrasing and so on. This opinion is also considered the most acceptable, notable and widespread over the days and ages because of its harmony with the superiority of the nation in terms of language and rhetoric in general when the inimitable Holy Quran was sent down. This has led to the theme of this research which will highlight one of the aspects of the wondrous nature of the Holly Quran which the scholars have dealt with in their books and correspondences, which is clarifying the effect of metaphor on the wondrous nature of the Quran. The research does so by discussing three books that have had a clear impact on the rhetoric study in general and on proving the wondrous nature of the Holy Quran through proof and evidence in particular, especially in the second and third book. These books are The Science of Metaphor by Abdullah Ibn Al Muataz, 396 A.H.; The wondrous Nature of the Quran by Al Baqlani, 403 A.H; and The Science of Metaphor in Quran by Ibn Alisbaa Al Masri, 654 A.H.